Proposal for magnetic resonance imaging-guided salvage radiotherapy for prostate cancer*. (2nd January 2017) - Dirix, Piet; van Walle, Lien; Deckers, Filip; Van Mieghem, François; Buelens, Guido; Meijnders, Paul; Huget, Philippe; Van Laere, Steven
Abstract: Background: A subset of patients experience a biochemical recurrence following radical prostatectomy. Radiotherapy can salvage those patients, provided that all disease is encompassed within the target volume. We hypothesized that this can be achieved more adequately with magnetic resonance imaging (MRI)-guided treatment planning. Material and methods: From January 2009 to April 2014, 183 patients were referred to our department for salvage radiotherapy (SRT). According to protocol, patients received a planning computed tomography (CT) as well as an MRI in treatment position. All MRI scans were retrospectively reviewed by an experienced uro-radiologist. Results: Median prostate-specific antigen (PSA) value at time of referral was 0.3 ng/ml (range 0.02–4.7 ng/ml). MRI did not show any suspected macroscopic disease in 137 patients (75%). In 46 (25%) patients, MRI did indicate a pelvic recurrence. The mean PSA level was significantly higher in patients with a suspected recurrence on MRI (0.4 vs. 1.4 ng/ml, p < .001) on a Student's t-test. The mean follow-up was 33 months (range 5–69 months). Biochemical disease-free survival (bDFS) was significantly worse in patients with suspected disease on MRI [hazard ratio (HR) 2.9, p < .0001]. bDFS was significantly worse in the subgroup where the macroscopic recurrences on MRI received a lower radiation dose (HR 3.4, p = .01). Conclusion: MRI detects loco-regional disease in a substantial subset of patients with a biochemical recurrence after prostatectomy, especially in a PSA above 0.5 μg/l. Lack of MRI-based dose escalation on these macroscopic recurrences could explain some of the biochemical progression observed after SRT.